2023
DOI: 10.1590/1806-9282.20221035
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of patients of vaccine side effects after the COVID-19 vaccine

Abstract: OBJECTIVE: Postvaccine side effects were evaluated in patients presenting to our emergency department with complaints of vaccine side effects after taking COVID-19 vaccine, and new unknown side effects ranging from mild complaints to life-threatening risks, and frequency of all side effects were investigated. This study aimed to establish a scientific resource to identify the potential side effects of the vaccine. METHODS: Patients' demographic information, clinical characteristics, epicrisis reports, COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…Many clinical studies have been shown that inactivated SARS-CoV-2 vaccines have a lower frequency of side effects compared to other types of vaccines [ 7 9 ]. Gedik MS et al reported that of the patients who attended the emergency department after vaccination, 86.9% complained after receiving the Pfizer-BioNTech vaccine (mRNA vaccine) and 13.1% after receiving the Sinovac vaccine [ 10 ]. Büyüker SM et al reported from 602 cases that complaints of physical discomfort and fever were more common in those who received the BioNtech vaccine than those who received the Sinovac vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Many clinical studies have been shown that inactivated SARS-CoV-2 vaccines have a lower frequency of side effects compared to other types of vaccines [ 7 9 ]. Gedik MS et al reported that of the patients who attended the emergency department after vaccination, 86.9% complained after receiving the Pfizer-BioNTech vaccine (mRNA vaccine) and 13.1% after receiving the Sinovac vaccine [ 10 ]. Büyüker SM et al reported from 602 cases that complaints of physical discomfort and fever were more common in those who received the BioNtech vaccine than those who received the Sinovac vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Upon evaluation in the emergency department, the most prevalent diagnoses were upper respiratory infection (28.6%) and myalgia (32.1%). Notably, none of the patients required ventilator support or hospitalization, and all were discharged 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Vaccination stands out as a paramount defense against viral infections [2]. Various vaccines, including mRNA, inactivated, and adenovirus vector-based, have been devised to combat COVID-19 [3]. One such vaccine, CoronaVac, an inactivated SARS-CoV-2 vaccine developed by Sinovac/Biotech, China, obtained global emergency use approval [4].…”
Section: Retrospective Analysis Of Healthcare Workers Admitted To Eme...mentioning
confidence: 99%